Microsatellite Genetic Markers of Saccharrum spp., and Erianthus sp. on Their Hybrids - Mala Murianingrum; Taryono Taryono; Rani Agustina Wulandari (Jurnal Ilmu Pertanian, 2018)
Progeny identification is the important step that should be done after hybridization. However, polyploidy, aneuploidy and the high chromosome segregation in sugarcane which results various phenotypic characteristics variation and environmental effects become limiting factors to identify the progenies based on morphological characteristic. Microsatellite as one of molecular marker which has codominance inheritance, multiallelic, abundant in the genome and does not influenced by environmental factor is the best tool to asses the crossing fidelity accurately. This research aimed to identify the possibility of genetic marker of Saccharum spp. and Erianthus sp. on their hybrid using microsatellite molecular marker. This study was carried out in Molecular Genetic laboratory, Indonesian Sweetener and Fiber Crops Research Institute (ISFCRI) Malang, from August 2016 to July 2017. Eighty-six (86) F1 intraspecific and interspecific progeny, three commercial sugarcane varieties (PSJT941, PS881 and VMC7616) and two wild types (S. spontaneum dan Erianthus sp.) were assessed genetically by three microsatellite markers. Identification of microsatellite genetic markers was conducted by comparing the visualization band results from electrophoresis of each male and female parent through their progenies. All primers could identify Saccharum spp. and Erianthus sp. genetic markers. There were one to eleven Saccharum spp. and Erianthus sp. genetic markers could be identified such as 2-11 PS881-specific alleles; 2-3 VMC7616-specific alleles; 1-5 PSJT941-specific alleles; two S. spontaneum-specific alleles and 1-2 Erianthus-specific alleles. These findings could be used as the advance genetic marker of microsatellite in sugarcane breeding to asses the cross fidelity.